2007
DOI: 10.1007/bf02932085
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic analysis ofBorrelia spp. isolated fromIxodes ricinus ticks by using electrophoretic chips and real-time polymerase chain reaction

Abstract: The genotype of Borrelia burgdorferi sensu lato was detected in 371 out of 1244 ticks. Borrelia determination was based on partial sequencing of the 16S rRNA gene and real-time polymerase chain reactions for identification and quantitation of ospA and recA genes. Different Borrelia spp. were identified; B. garinii in 40% ticks followed by B. afzelii (36.3%), B. burgdorferi sensu stricto (12.9%), B. valaisiana (3.5%), B. lusitaniae (0.8%), B. bissettii (0.5%) and B. miyamotoi-like (0.5%). Cultivation of 30 borr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 24 publications
1
17
0
1
Order By: Relevance
“…complex in Europe (Piesman and Gern, 2004;Rauter and Hartung, 2005). At the opposite pole (with only one MLST profile retrieved from literature) was B. bissettii, a genospecies relatively common in North America (Bissett and Hill, 1987;Oliver et al, 2003), but that has been seldom found in Europe (Fingerle et al, 2008;Hulinska et al, 2007;Strle et al, 1997). The low frequency of B. spielmanii, and B. lusitaniae could be explained by the low relative abundance and patchy habitats of the competent transmission vertebrates for those genospecies -dormice and lizards (Majlathova et al, 2006;Richter and Matuschka, 2006;Richter et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…complex in Europe (Piesman and Gern, 2004;Rauter and Hartung, 2005). At the opposite pole (with only one MLST profile retrieved from literature) was B. bissettii, a genospecies relatively common in North America (Bissett and Hill, 1987;Oliver et al, 2003), but that has been seldom found in Europe (Fingerle et al, 2008;Hulinska et al, 2007;Strle et al, 1997). The low frequency of B. spielmanii, and B. lusitaniae could be explained by the low relative abundance and patchy habitats of the competent transmission vertebrates for those genospecies -dormice and lizards (Majlathova et al, 2006;Richter and Matuschka, 2006;Richter et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Another tick species D.r. is involved in transmision of F. tularensis, C. burnetii, B. canis, and the H.c. tick could transmit Flavivirus of tick-borne encephalitis in European conditions (Hubálek and Rudolf 2007;Hulínská et al 2007). …”
mentioning
confidence: 99%
“…The addition of a 269-nt amplicon of the p66 gene and a 93-nt amplicon of the ospA sequence to the concatenated sequences confirmed the separation of all spirochete species into two groups. (20,35,54,56,57,61). The last decade of the 20th century brought a significant increase in the number of identified Borrelia strains in the United States (1,5,34,37,51,66).…”
mentioning
confidence: 99%